2019
DOI: 10.1007/s12350-017-1121-7
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for the quantification of inflammation in large carotid artery plaques

Abstract: Background. There is currently no consensus on the methodology for quantification of 18 F-FDG uptake in inflammation in atherosclerosis. In this study, we explore different methods for quantification of 18 F-FDG uptake in carotid atherosclerotic plaques and correlate the uptake values to histological assessments of inflammation.Methods and Results. Forty-four patients with atherosclerotic stenosis ‡70% of the internal carotid artery underwent 18 F-FDG PET/CT. Maximum standardized uptake values (SUV max ) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 35 publications
3
32
1
Order By: Relevance
“…Our interpretation of this finding is that the plaque inflammation we can detect with 18 F-FDG PET is homogeneously spread out, and also present in the extreme tails of the plaque. This was also one of our main findings when we explored associations between different 18 F-FDG uptake parameters and plaque inflammation at histopathology [17]. Furthermore, this is in accordance with the study results from Kwee et al [12] who found a strong correlation between TBRs of ipsilateral symptomatic plaques and contralateral asymptomatic plaques and supports the hypothesis that plaque inflammation is systemic to some extent.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our interpretation of this finding is that the plaque inflammation we can detect with 18 F-FDG PET is homogeneously spread out, and also present in the extreme tails of the plaque. This was also one of our main findings when we explored associations between different 18 F-FDG uptake parameters and plaque inflammation at histopathology [17]. Furthermore, this is in accordance with the study results from Kwee et al [12] who found a strong correlation between TBRs of ipsilateral symptomatic plaques and contralateral asymptomatic plaques and supports the hypothesis that plaque inflammation is systemic to some extent.…”
Section: Discussionsupporting
confidence: 90%
“…A strength of our study is a relatively large patient population with a wide range of uptake values (max SUV max from 1.18 to 2.66) representing low to high plaque inflammatory activity confirmed by histology [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Johnsrud et al 1 recruited 44 patients with carotid artery atherosclerosis associated with[70% stenosis for 18 F-FDG PET/CT. Of these patients, 30 underwent endarterectomy and histological assessment of inflammation to evaluate the correlation between different 18 F-FDG uptake quantification methods and histological indices of inflammation.…”
Section: Uptake Quantificationmentioning
confidence: 99%
“…In this issue of the Journal of Nuclear Cardiology, Johnsrud et al 1 have explored the correlation between different quantification methods of 18 F-fluorodeoxyglucose ( 18 F-FDG) uptake and plaque inflammation in endarterectomy specimens of patients with severe carotid stenosis. It has been over a decade since the initial reports of 18 F-FDG accumulation in unstable carotid plaques and its correlation with indices of plaque vulnerability.…”
mentioning
confidence: 99%